The Typology of Settlement Development in Riverbanks in Pontianak - Bambang Soemardiono; Dewi Septanti; Ivan Gunawan (International Journal of Environment, Architecture, and Societies, 2022)
The development of Pontianak begins from the influence of the existence of the Kapuas River and its tributaries. The river used to be a space for community activities, with many houses and villages built based on their proximity to the river. The settlement grew to fill the land on the banks of Kapuas River first until they spread to its tributaries. This research aims to identify the typology of settlement development in riverside communities in Pontianak from time to time. This research employed a qualitative method with a comparative study. The researcher collected secondary data in the form of a map of the condition of settlements in Pontianak from time to time obtained from the historical records of Pontianak. Then, the data were compared and analyzed to obtain a typology of settlement development in the riverside communities in Pontianak. The study’s results, namely the typology of settlements on the riverbanks in Pontianak, revealed the settlements that follow the structure of the riverbanks, ditch canals, and the settlements that lead to land roads. This can happen because of an increase in the number of people every year, accessibility range, and economic movement factors.